2014
DOI: 10.1007/s00192-014-2485-8
|View full text |Cite
|
Sign up to set email alerts
|

Mixed urinary incontinence: international urogynecological association research and development committee opinion

Abstract: The diagnosis of MUI encompasses a very heterogeneous group of women. The evaluation and treatment requires an individualized approach. The use of validated questionnaires is recommended to assess urinary incontinence symptoms and effect on quality of life. Conservative therapy is suggested as a first-line approach; if surgery is contemplated, urodynamic investigation is recommended. Women undergoing surgical treatment for MUI need to be counselled about the possibility of persistence of urinary urgency, frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 68 publications
0
35
0
4
Order By: Relevance
“…UI affects 10e40% of women, with the most common type known as stress urinary incontinence (SUI) [2]. Risk factors for SUI include increased number of vaginal deliveries, obesity, previous hysterectomy, chronic cough, poor health, depression, and stroke [1].…”
Section: Introductionmentioning
confidence: 99%
“…UI affects 10e40% of women, with the most common type known as stress urinary incontinence (SUI) [2]. Risk factors for SUI include increased number of vaginal deliveries, obesity, previous hysterectomy, chronic cough, poor health, depression, and stroke [1].…”
Section: Introductionmentioning
confidence: 99%
“…Research has revealed that both SUI and UUI are more prevalent among patients who experience increase in BMI 6. In accordance, obese and overweight patients tend to undergo surgical treatment for UI more frequently than normal-weight patients 20.…”
Section: Discussionmentioning
confidence: 98%
“…MUI is the involuntary loss of urine associated with urgency as well as with effort or physical exertion or on sneezing or coughing. Treatment depends on the type of UI, but all types appear to benefit from fluid restriction, regulation of diuretics and other drugs, pelvic floor and Kegel exercises, as well as weight loss 6. Whereas primary treatment of UUI comprises antimuscarinic pharmacotherapy, treatment of SUI via pharmaceutical therapy is more limited, with surgical methods such as placement of a midurethral sling being most commonly used 7…”
Section: Introductionmentioning
confidence: 99%
“…39 Although pelvic floor muscle exercises are included in UUI treatment, bladder training and strategies to promote skills and behaviors that encourage continence are also critical. 13, 40 …”
Section: Methodsmentioning
confidence: 99%
“…UUI is thought to be a result of involuntary detrusor muscle contractions, although many women with UUI do not demonstrate detrusor overactivity on urodynamic testing. 13 Primary treatments for UUI are typically behavioral and/or medical.…”
Section: Introductionmentioning
confidence: 99%